Comparative Nutritional Profiling of Economically Important Shrimp Species in Pakistan - Muhammad Bhatti; Shahid Sherzada; Sohail Ahmad; Muhammad Qazi; Amina Ayub; Saeed Khan; Muhammad Khan; Iqra Rani; Nimra Hussain; Joanna Nowosad; Dariusz Kucharczyk (Journal of Marine Science and Engineering, 2025)
Shrimp are widely recognized as a nutritious and flavorful food choice due to their tender and delicious meat. This study evaluated the nutritional composition of three economically important shrimp species: Penaeus merguiensis, Penaeus monodon, and Penaeus indicus, collected from the coastal areas of Pakistan. All shrimp species were found to be high in protein and low in fat content. The ratio of essential amino acids (EAAs), non-essential amino acids (NEAAs), and total amino acids (TAAs) varied significantly (p ≤ 0.05) among species, with P. indicus showing slightly higher values. Regarding fatty acid analysis, total saturated fatty acid content was found to be 35.04% in P. merguiensis, 52.43% in P. monodon, and 44.77% in P. indicus. Similarly, the polyunsaturated fatty acid content was found to be 26.24%, 26.77%, and 24.74%, in P. merguiensis, P. monodon, and P. indicus, respectively. Based on nutrient yield, P. monodon stands out as the most nutrient-dense species, followed by P. indicus and P. merguiensis. Overall, the present study suggests that all shrimp species can be used as a healthy choice of food and a good source of animal protein for human consumption. These findings provide valuable insights into the role of shrimp in promoting a healthy and balanced diet.